Effects of varied amount of carbon dioxide and pressure on asphaltene stability - Janier, J.B. (American-Eurasian Network for Scientific Information, 2014)
Background: Asphaltene precipitation and deposition from crude oils is one of the issues for the oil industry. The deposition occurs during production, transportation and separation process. Injection of carbon dioxide (CO2) during enhance oil recovery is believed to contribute much to the precipitation of asphaltene and it can significantly be affected by the changes in pressure and temperature of the crude oil. Reduction in pressure contributed much to the instability of asphaltene as compared to reduction in temperature. This paper investigated the effect of change in pressure with constant temperature at reservoir condition by varying the amount CO2 injected into the light crude oil sample towards the stability of asphaltene. Results: The experimental saturation pressure for 18cc CO2 injected into 45cc light oil was 1498.375psi and with asphaltene onset point of 1620 psi. For 27cc CO2 injected into 45cc light oil, the saturation pressure was 2046.502psi and with asphaltene onset point of 2230psi. Furthermore, the asphaltene onset point was predicted to occur at pressure slightly higher than the saturation pressure. Conclusion: As the amount of injected CO2 increased, the saturation pressure increased and will accelerate the precipitation of asphaltene. Reduction in pressure significantly affected the stability of asphaltene at constant temperature. The asphaltene precipitation started to occur at pressure slightly above the saturation pressure. Â© 2014 AENSI Publisher All rights reserved.